Civility and subversion : the intellectual in democratic society - Goldfarb, Jeffrey C. (Cambridge University Press, 1998)
The book provides a sophisticated alternative to existing accounts of the role of the intellectual in modern democracy. Arguing that society suffers from a systemic deliberation deficit. Jeffrey Goldfarb explores the potential of the intellectual as democratic agent, at once civilizing political contestation and subverting complacent consensus. Professor Goldfarb deploys classical and contemporary social theory to analyze a diverse set of intellectuals in action, from Socrates in fifth-century Athens to Malcolm X and Toni Morrison in twentieth-century America, and, drawing on personal acquaintance, the political dissidents in communist and post-communist Central Europe.